2022
DOI: 10.21203/rs.3.rs-2022168/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inhibition of Notch pathway Alleviates nab-Paclitaxel-Induced Peripheral Neuropathic Pain in Rats via Suppressing HMGB1/TLR4 Signaling in Spinal Cord

Abstract: Paclitaxel is widely used in clinical treatment of cancer and peripheral neuropathy is a common adverse side effect of paclitaxel. Diverse mechanisms contribute to the development and maintenance of paclitaxel-induced peripheral neuropathy. However, the role of spinal notch pathway in paclitaxel-induced peripheral neuropathy is not completely understood. In this study, we established an animal model of paclitaxel-induced peripheral neuropathy using nab-paclitaxel. We found that the mechanical and thermal pain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Microglia and astrocytes are also most affected by a reduction in the inflammatory response [ 26 ]. Our previous study also found that inhibition of the Notch pathway could reduce the expression of inflammatory factors accompanied by repressive glia response through the HMGB1/TLR4 signalling pathway in a rat model of nab-paclitaxel-induced peripheral neuropathy [ 27 ]. All the results suggested that TPPU may suppress the activation of the glial response through the regulation of inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Microglia and astrocytes are also most affected by a reduction in the inflammatory response [ 26 ]. Our previous study also found that inhibition of the Notch pathway could reduce the expression of inflammatory factors accompanied by repressive glia response through the HMGB1/TLR4 signalling pathway in a rat model of nab-paclitaxel-induced peripheral neuropathy [ 27 ]. All the results suggested that TPPU may suppress the activation of the glial response through the regulation of inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%